Consent Documentation and the Accessibility of Research Results in International Development Research - Malich, Erika (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
This case study touches on issues that may arise in international development research, with reflections based on experiences conducting research in Peru. The two issues to be discussed are that of cultural differences in the consent documentation process, and ensuring that the benefits of research flow back to research participants.